Write the equation of the circle in standard form
x2 + y2 + 6x – 18y + 74 = 0
Move the constant to the right side and group like terms on the left side.
x2 + y2 + 6x - 18y + 74 = 0
(x2 + 6x) + (y2 - 18y) = -74
Set the equation up to complete the square.
(x2 + 6x +___) + (y2 - 18y +___)
= -74 + __+__
Add (b/2)2 to complete the square for x. Add (b/2)2 to complete the square for y.
(x2 + 6x +________) + (y2 - 18y + ___)=-74 + ____ + ____
Simplify (x2 + 6 + __) + (y2 - 18y + ---) = 16. Factor ___2 + ___2)= 16